Juana of Castile’s Book of Hours: An Archduchess at Prayer - Twomey, Lesley K. (Religions, 2020)
This article examines one of Juana of Castile’s books of hours (London, BL Add. MS 18852) comparing it with those written for members of Juana’s family and seeking to discern how it was used, in order to reassess her peers’ evaluation of her spiritual affinities. It considers how Juana customized her book of hours with a miniature of the Virgin and Child, comparing it with a gifted panel painted by Rogier van der Weyden that Juana treasured to show how she placed herself under the protection of the Virgin. Numbered precepts would be intended for her to instruct any future children and are replicated in Isabel, her daughter’s, book. The office of the Guardian Angel is compared with similar ones in Spain and Burgundy and, like devotion to St Veronica, such prayer is another means of protection. The striking mirror of conscience with its reflected skull, like other similar objects decorated with a skull that Juana possessed, sought to lift her from the decay and sinfulness of the world to the spiritual realm.